Państwo jako podmiot odpowiedzialny za zbrodnie międzynarodowe = State as a subject responsible for international crimes - Bernacka, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article describes the formation process of State responsibility under International Law and it further analyses the issue of the responsibility in the light of the Draft Articles on responsibility of States for Internationally Wrongful Acts prepared by the International Law Commission in 2001.
Keywords: państwo - teoria; prawo; zbrodnie międzynarodowe